Validation of the procedure for determination of amino acids composition of glatiramer acetate by C-13 NMR spectroscopy - N. E. Kuz’Mina; S. V. Moiseev; V. I. Krylov; A. A. Kutin; E. A. Zhukov; V. A. Yashkir; V. A. Merkulov (Регуляторные исследования и экспертиза лекарственных средств)
The article describes validation of the procedure for determination of amino acids composition of glatiramer acetate by C-13 NMR spectroscopy. The procedure makes it possible to determine the molar ratio of amino acids present in glatiramer acetate with no need for a reference standard. The authors evaluated the accuracy, linearity, repeatability, intermediate precision and specificity of the validated procedure. The analysis of extraction factors for L-Glu, L-Ala, L-Tyr и L-Lys helped to calculate the systematic errors, standard deviations, confidence intervals, variation coefficients, confidence intervals, Fisher’s test and Student’s t-test for the results of amino acids molar ratio determination. It was shown that the obtained statistical data satisfy the acceptance criteria for validation parameters described in the national and foreign quality standards.